PENGARUH PROMOSI, DESAIN TEMPAT DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DISETARA COFFEE BATAM - BAHRI, NUR IRPAN; Raymond, Raymond (SCIENTIA JOURNAL, 2021)
This study aims to analyze the effect of promotion, place design and service quality on coffee purchasing decisions at Setara Coffee Batam. This type of research is a quantitative research, using purposive sampling as many as 100 respondents, processed using SPSS version 25 with the results of the study known that the t- count is 4.088 > 1.664 and the significance value is 0.000 < 0.05, which means that promotion has a positive and significant effect on purchasing decisions. The design of the place is known to have t-count -1.425 < 1.664 and a significance value of 0.157 > 0.005, which means that the design of the place has no effect on purchasing decisions. The quality of service is known to t-count 6.972 > 1.664 and a significance value of 0.000 < 0.05, meaning that service quality has a positive and significant effect on purchasing decisions. Then there is a positive and significant influence simultaneously (together) between promotion, place design and service quality on consumer purchasing decisions at Setara Coffee Batam can be seen from the F value of 103.175 (F count) > 2.70 (F table) with significance value 0.000 < 0.05.